From Seven Years to 360 Degrees: Primitive Accumulation, the Social Common, and the Contractual Lockdown of Recording Artists at the Threshold of Digitalization - Matt Stahl (tripleC: Communication, Capitalism & Critique)
This article examines the apparent paradox of the persistence of long-term employment contracts for cultural industry ‘talent’ in the context of broader trends toward short-term, flexible employment. While aspirants are numberless, bankable talent is in short supply. Long-term talent contracts appear to embody a durable axiom in employment: labor shortage favors employees. The article approaches this axiom through the lens of recent reconsiderations of the concept of primitive accumulation. In the case of employment, this concept highlights employers’ impetus to transcend legal and customary barriers to and limits on their capacity to capture and compel creative labor, and to appropriate the products of contracted creative labor. The article supports this argument through the analysis of contests between Los Angeles-based recording artists and record companies over the California and federal laws that govern their power and property relations. These struggles reveal a pattern of attempts by record companies to overcome or change laws that limit their power to control, compel and dispossess recording artists. The article suggests that as contractual forms change under digitalization, familiar political dynamics continue to characterize the relationships between recording artists and the companies that depend on their labor and output.